Pemasangan Lampu Jalan dan Pembangunan Pembangkit Listrik Berbasis Solar Cell Sebagai Prototype Pembelajaran Energi Terbarukan Di MA Al-Khairiyah Rancaranji - Septianissa Azzahra; Samsurizal Samsurizal; Christiono Christiono; Miftahul Fikri (Terang, 2020)
Renewable energy, especially solar power plants (PLTS), is now begin to develop their applications to many forms, such as: installed as a home power supply, power supply for buildings, and also as power supply for street lighting (solar street light). Madrasah Aliyah Al-Khairiyah Rancranji In this regard, as a partner, demand a socialization and a study for their students to understand more about renewable energy topics especially about solar energy. And the limited electric power is also one of the problems for this school. Therefore, PKM activity in Madrasah Aliyah Al-Khairiyah Rancaranji is a solution given by the PKM team by providing learning and an introduction of renewable energy as well as workshop and installation of PLTS and road lamps based on solar cell. Results gained after the implementation of this activity are students understand and knows about the renewable energy, its application and its benefits in daily life.